2000
DOI: 10.1345/aph.19269
|View full text |Cite
|
Sign up to set email alerts
|

Miglitol: Assessment of its Role in the Treatment of Patients with Diabetes Mellitus

Abstract: Miglitol is an effective and safe treatment option in patients with type 2 diabetes mellitus who are inadequately controlled with diet or oral sulfonylurea therapy. Miglitol is a good choice of therapy in Hispanic, African-American, and elderly patients, or any patients in whom hypoglycemia, weight gain, or lactic acidosis are risks. No published studies comparing miglitol with acarbose have been published, but there appears to be no major clinical or financial advantages to using one agent over the other.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(45 citation statements)
references
References 33 publications
0
44
0
1
Order By: Relevance
“…Voglibose has not been subject to a literature review. It is difficult to value the results of these reviews because all have methodological weaknesses: no description of search strategy and inclusion criteria (5)(6)(7), no report of search results (5)(6)(7)(8)(9), and they either lack or have an unclear quality assessment of the included studies (5)(6)(7)(8)(9). In general, all reviews reported beneficial effects on glycemic control.…”
mentioning
confidence: 99%
“…Voglibose has not been subject to a literature review. It is difficult to value the results of these reviews because all have methodological weaknesses: no description of search strategy and inclusion criteria (5)(6)(7), no report of search results (5)(6)(7)(8)(9), and they either lack or have an unclear quality assessment of the included studies (5)(6)(7)(8)(9). In general, all reviews reported beneficial effects on glycemic control.…”
mentioning
confidence: 99%
“…Miglitol was used as a standard inhibitor molecule for the comparison as it was alone capable of satisfying all the five rules of Lipinski in comparison to acarbose, metformin, and voglibose standards [33,34]. The ligand molecules along with the standard miglitol were docked into the binding pockets of α-amylase and α-glucosidase to find out their binding interactions.…”
Section: Molecular Docking Analysismentioning
confidence: 99%
“…Two different AGIs were used: acarbose (Bayer, West Haven, CT), which is not absorbed by the small intestine, and deoxynojirimycin (1-deoxynojirimycin hydrochloride, Sigma-Aldrich), which, like its closely related analog miglitol, is absorbed [14][15][16] by active transport [17]. Both compounds have a very high affinity for intestinal glucosidases [18].…”
Section: A-glucosidase Inhibitorsmentioning
confidence: 99%